Global elites the opaque nature of transnational policy determination - Kakabadse, Andrew; Kakabadse, Nada (Palgrave Macmillan, 2012)
Exploring the nature, configuration and influence of global elites, this book examines the impact of elites on transnational policy development and strategically on corporations as board members of PLCs and international joint ventures. Overall, the book provides a balanced view of how our present day elites operate.